Evaluasi Metode Penilaian Persediaan Tanah pada Perusahaan Properti - Andi Wawo (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2015)
This study aims to analyze and provide empirical evidence that valuation method by specific identification method, Fisrt in Firs out Method, Weigted Average Method and lower cost and Net realizable value method to determine value inventory estate. This study using descriptive analasis to analyze and the result showed that specific identification method, Fisrt in Firs out Method, Weigted Average Method and lower cost and Net realizable value method not precisely to determine value inventories estate but revaluation method is precisely to determine value inventories estate on financial statement.